Silver (I) coordination chemistry: from 1-D chains to molecular rectangles - Abul-Haj, Mohammad; Aakeröy, Christer B.; Desper, John (My University, 2012)
A series of silver(I) coordination compounds with the ligand 2-(4-pyridyl)imidazole 4-PyIm has been synthesized and crystallographically characterized in order to explore the role of counter ion, solvent and ligand charge on the resulting supramolecular architectures. With perchlorate and hexaflourophosphate, two iso-structural 1-D coordination-polymers were obtained, but when changing the counter ion to nitrate and using water as solvent, an unusual molecular rectangle composed of four ligands and four Ag(I) ions was obtained, and the assembly was controlled by hydrogen bonding via the anion and water molecules. Finally, when the ligand was deprotonated, the change in the number of binding sites (from two to three) was reflected in an increase in coordination number for the silver ion.
Keywords: Silver(I); 4-PyIm; Crystal engineering; Supramolecular chemistry; Molecular rectangles